Investment of Waqf Funds in Malaysia: A Descriptive Study of Cultivating Uncultivated Land from Public Interest Perspective - Mahmoud Mohamed Ali Mahmoud Edris; Mohamed Sharif Bashir Elsharif; Yusuf Sani Abubakar; Saeed Ahmed Saleh Farag; Sami Khalaf Salim Al Bzeirat (International Journal of Religion, 2024)
Non-Indexed Publication